Temperatures for germination of Tabebuia ochracea (Cham.) Standl seeds - Oliveira, Ademir Kleber Morbeck; Ribeiro, Jonathan Wesley Ferreira; Pereira, Kelly Cristina Lacerda; Silva, Cássila Andréia Araújo (Comunicata Scientiae, 2012)
The Tabebuia ochracea species is an ornamental tree when in full bloom and its wood, very hard and resistant, is used in construction, manufacture of railway sleepers and poles, among other uses and is one of the most commonly used species in reforestation project. The objective of this study was to evaluate the germination of seeds of T. ochracea under different temperatures. Germination tests were conducted with four sub-samples of 50 seeds in a Petri dish lined with paper germitest, kept in BOD chambers where they were tested for germination following constant temperatures: 20, 25, 30, 35, 20-30 e 25-35 ºC. The experimental design was completely randomized design with four replications of 50 seeds. The data expressed in percentages and means compared by Tukey test at 5% probability. The T. ochracea showed a broad range of germination between the temperatures studied, upper 93%. The best speed of germination and mean germination time were found at temperatures of 25, 30 and 35 oC. The measures of dry weight and length of primary root showed equal growth rate for all temperatures.